Petrology and Sedimentation of the Archean Seine Group Conglomerate and Sandstone, Western Wabigoon Belt, Northern Minnesota and Western Ontario - Frantes, James R (1987)
A Thesis submitted to the faculty of the Graduate School of the University of Minnesota by James R. Frantes in partial fulfillment of the requirements for the degree of Master of Science, February 1987. Plates 1-2 referenced in the thesis are also attached to this record. The Seine Group conglomerate and sandstone are part of the Wabigoon Volcanic Superbelt (Subprovince), located in northern Koochiching County in Minnesota and the Fort Frances-Mine Centre area in western Ontario. This fault-bound wedge of complexly interbedded rocks, that comprises a belt of Archean metasedimentary and metavolcanic rocks, is located north of the Rainy Lake-Seine River Fault and south of the Quetico Fault. The Seine Group occupies a narrow belt both in Minnesota (approximately 16 km by 0.9 km), and in Ontario (approximately 36 km by 2 km). The sedimentary rocks of the Seine Group include orthoconglomerate, feldspathic sandstone, and minor mudstone and banded iron-formation. A. C. Lawson was the first to record geological investigations in the area. Poulsen and others suggested the Keewatin metavolcanic unit is the oldest unit in the area. The Seine Group nonconformably overlies the metamorphosed plutonic rocks (Lawson's Laurentian) in the eastern part of the study area near Mine Centre. All rocks in the area have undergone at least greenschist facies metamorphism. Bedding consistently strikes east-northeast and dips nearly vertical. Foliation has a similar trend throughout the study area. Criteria such as cross-bedding, graded bedding, load casts, and vesicular texture in the tops of lava flows usually indicate top to the south. Lineations are usually found in the foliation plane and vary in plunge from 30-70 degrees to the east-northeast. In the eastern part of the study area, clasts within the conglomerate are more deformed than the conglomerate clasts in the western part of the study area. Megascopic modal analyses, carried out on field exposures, showed that volcanic cobbles and pebbles are the most abundant clasts, usually ...